If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (19x + 6)(20x) = 0 Reorder the terms: (6 + 19x)(20x) = 0 Remove parenthesis around (20x) (6 + 19x) * 20x = 0 Reorder the terms for easier multiplication: 20x(6 + 19x) = 0 (6 * 20x + 19x * 20x) = 0 (120x + 380x2) = 0 Solving 120x + 380x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '20x'. 20x(6 + 19x) = 0 Ignore the factor 20.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(6 + 19x)' equal to zero and attempt to solve: Simplifying 6 + 19x = 0 Solving 6 + 19x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 19x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 19x = 0 + -6 19x = 0 + -6 Combine like terms: 0 + -6 = -6 19x = -6 Divide each side by '19'. x = -0.3157894737 Simplifying x = -0.3157894737Solution
x = {0, -0.3157894737}
| 0=3x^2+1 | | 5m^2+13m+15=0 | | f(x)=5x^2+10x+1 | | x^3-5x^2-5x-1=0 | | 3y-9y+5w+w= | | c/4+3=8 | | 5-1k=21-3k+12 | | (51x+3)(1+52x)= | | X/8-6=8 | | 5+x/8=-3 | | (x+2x^3-3)/(x-1)=0 | | .5x+16(x+2)=48.5 | | 5x-11=10+12x | | (x+2x^3-3)/(x-1) | | x^4-9x^2-52=0 | | 3+y=19 | | 2z-3-2(1+z)=-5 | | Y=-2/5 | | 2x/3-2=4 | | -7x+1=57 | | x/4.6=-2.5 | | 4X^2+8X-180=0 | | (C+5)/2=18 | | 2(x-7)=35 | | 5y^3-20y^2+y-4= | | x^2-3x+85=0 | | x-2/3=2x+11 | | 5u+5(1+u)=u+8 | | s+x=16 | | x^3+x-17=0 | | x^2-12x+40= | | 10x=185-5y |